Tindak Tutur Ekspresif Anak-Anak Dalam Lingkungan Kelompok Bermain di Wilayah H. Saemin Pondok Pinang - Nisa, Aprilda Chairun (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to analyze and describe the forms of expressive speech acts produced by children playing in the H. Saemin area, Pondok Pinang. The method used is the observe-note-classify-analyze method with data collection techniques through observation. From the research results, conversation data was obtained for 7 illocutionary speech acts in the category of expressive speech acts. Through 7 conversation data from children with the initials RKY (K), RZA (Z), ADN (D), and AZM (A), 15 expressive utterances were obtained in the data game, including expressions of greeting, insulting, blaming, thanking. love, complain, praise, apologize and criticize.